Low levels of organic compound trace elements improve the eggshell quality, antioxidant capacity, immune function, and mineral deposition of aged laying hens - K.K. Zhang (Elsevier, 2021)
In the egg production industry, trace elements are required as additional dietary supplements to play vital roles in performance and egg quality. Compared to inorganic microelements (ITs), appropriate dose of organic trace microelements (OTs) are environmentally friendly and sufficient to satisfy the needs of hens. In order to evaluate the extent to which low-dose OTs replace whole ITs, the effects of organic copper, zinc, manganese, and iron compound on the performance, eggshell quality, antioxidant capacity, immune function, and mineral deposition of old laying hens were investigated. A total of 1 080 57-week-old Jing Hong laying hens were assigned to five groups with six replicates of 36 layers each for an 8-week experimental period. The birds were fed either a basal diet (control treatment (CT)) or the basal diet supplemented with commercial levels of inorganic trace elements (IT 100%) or the equivalent organic trace elements at 20%, 30%, and 50% of the inorganic elements (OT 20%, OT 30%, and OT 50%, respectively). Results showed that compared with those in the CT treatment, feeding hens with inorganic or organic microelement diet had significant effects on the eggshell quality, antioxidant capacity, immune function, and mineral deposition of old laying hens (P < 0.05). The eggshell strength and ratio between OT 30%, OT 50%, and IT 100% were similar at weeks 4 and 8, and the eggshell thickness of these groups was also similar at weeks 6 and 8. At week 8, the eggshell colour in OT 50% was darker than that in IT 100%. The mineral content in the eggshells of OT 50% and IT 100% significantly increased (P < 0.001), with no significant difference in effective thickness, mammillary thickness, and mammillary knob width between groups. There were no differences in the malondialdehyde content, total antioxidant capacity, and total superoxide dismutase activity in serum between OT 30%, OT 50%, and IT100%. While the catalase activities, the interleukin-1β, interleukin-10, immunoglobulin G, and immunoglobulin M concentrations in serum were not significantly different between OT 50% and IT 100%. The mineral contents in the faeces of the organic groups were considerably reduced compared with those in IT 100% (P < 0.001). In conclusion, dietary supplementation with 30–50% organic compound microelements has the potential to replace 100% inorganic microelements in the hen industry for improving eggshell quality, mineral deposition in the eggshell, antioxidant capacity, and immune function, and reducing emissions to the environment without negative effects on laying performance.